2005
DOI: 10.1007/s11033-005-2312-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for Mcm10 in DNA Replication Initiation and Silencing at the Mating-type Loci

Abstract: Recent studies linking DNA replication proteins to transcriptional silencing suggest that some of the same mechanisms that facilitate the initiation of replication at origins might be involved in establishing repressed chromatin at silencer elements. Our ongoing studies of several mutants of the replication initiation factor Mcm10 of budding yeast revealed an associated defect in the production of mating type pheromones. This observation prompted us to look more directly at the effect of MCM10 mutations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Moreover, the possible reason similar defects are not observed in the Mcm10 d08029 allele is due to the fact that the S-phase delay is not severe enough in the early embryo to manifest as a defect. However, given that Mcm10 has been shown to have multiple roles in S phase, then it is more likely that the differences in these early embryos are a reflection of these additional Mcm10 functions (Wohlschlegel et al 2002;Gregan et al 2003;Lee et al 2003;Bielinsky 2004, 2006;Sawyer et al 2004;Douglas et al 2005;Liachko and Tye 2005;Zhu et al 2007;Park et al 2008a,b;Liachko and Tye 2009;Xu et al 2009). In light of previous studies that demonstrated a role for Mcm10 in chromosome condensation, interaction with Hp1, and defects in heterochromatin formation (Christensen and Tye 2003;Tye 2005, 2009), it is compelling to speculate that the defects observed in early embryos may not be due only to a direct role in DNA replication for Mcm10 but may also reflect a role in chromosome condensation and heterochromatin formation during S phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the possible reason similar defects are not observed in the Mcm10 d08029 allele is due to the fact that the S-phase delay is not severe enough in the early embryo to manifest as a defect. However, given that Mcm10 has been shown to have multiple roles in S phase, then it is more likely that the differences in these early embryos are a reflection of these additional Mcm10 functions (Wohlschlegel et al 2002;Gregan et al 2003;Lee et al 2003;Bielinsky 2004, 2006;Sawyer et al 2004;Douglas et al 2005;Liachko and Tye 2005;Zhu et al 2007;Park et al 2008a,b;Liachko and Tye 2009;Xu et al 2009). In light of previous studies that demonstrated a role for Mcm10 in chromosome condensation, interaction with Hp1, and defects in heterochromatin formation (Christensen and Tye 2003;Tye 2005, 2009), it is compelling to speculate that the defects observed in early embryos may not be due only to a direct role in DNA replication for Mcm10 but may also reflect a role in chromosome condensation and heterochromatin formation during S phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently evidence has been uncovered that points to an involvement of Mcm10 in chromatin structure. Work using S. cerevisiae has demonstrated that Mcm10 is involved in transcriptional repression of the matingtype loci and links DNA replication proteins to heterochromatin formation (Douglas et al 2005;Tye 2005, 2009). Also pointing to a possible role in chromatin structure and chromosome condensation is that the depletion of Mcm10 in Drosophila tissue culture cells results in undercondensed metaphase chromosomes (Christensen and Tye 2003).…”
mentioning
confidence: 99%
“…At restrictive temperature, mcm10 cells arrest at the end of S phase with aberrant DNA structures (Merchant et al 1997;Kawasaki et al 2000). Recently, Mcm10 has been implicated to function in chromatin structure in yeast as well as Drosophila melanogaster (Christensen and Tye 2003;Douglas et al 2005;Liachko and Tye 2005). In Drosophila, Mcm10 interacts with HP-1, an important heterochromatin protein (Christensen and Tye 2003), while in yeast Mcm10 interacts with Sir2 (Douglas et al 2005;Liachko and Tye 2005).…”
mentioning
confidence: 99%
“…Recently, Mcm10 has been implicated to function in chromatin structure in yeast as well as Drosophila melanogaster (Christensen and Tye 2003;Douglas et al 2005;Liachko and Tye 2005). In Drosophila, Mcm10 interacts with HP-1, an important heterochromatin protein (Christensen and Tye 2003), while in yeast Mcm10 interacts with Sir2 (Douglas et al 2005;Liachko and Tye 2005). In addition, genetic experiments suggest that the silencing function of Mcm10 is separate from its replication function (Douglas et al 2005;Liachko and Tye 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation